Impacts of small-scale irrigation on farmers’ livelihood: evidence from the drought prone areas of Upper Awash Sub-Basin, Ethiopia - Maru, H.; Haileslassie, Amare; Zeleke, T. (Elsevier, 2023)
Irrigation is an important mechanism to mitigate risks associated with the variability in rainfall for the smallholder subsistence farming system. This study analyzed how practicing small-scale irrigation (SSI) impacts the key livelihood assets on farm households’ human, physical, natural, financial, and social capitals in Ethiopia’s upper Awash sub-basin. The household-level survey data, collected from the 396 sample households, was used to carry out the current study. A Propensity Score Matching (PSM) analytical model was applied to match the SSI user and nonuser groups. The difference between the five capital assets of livelihood was estimated using the PSM’s Nearest Neighbor, Radius, Kernel Mahalanobis, and Stratification matching criteria. The results indicated that farmers’ participation in SSI has enhanced the capital assets of the farm households. Compared to the non-users, the irrigation users were better off in the number variety of food consumed (0.28 ± 0.13 Standard Error [SE]), types of crops produced (0.60 ± 0.17 SE), expenditures on land renting, and agricultural inputs (3118 ± 877 SE) measured in Ethiopian Birr (ETB), as well as on-farm (9024 ± 2267 SE ETB) and non-farm (3766 ± 1466 SE ETB) incomes. Challenges such as the involvement of local brokers in the market value chain and the absence of farmers’ marketing cooperatives have reduced the benefit of irrigated agriculture. Hence, the expansion of SSI schemes for the non-user farmers should consider improving the water usage mechanism and productivity, establishing proper water allocation institutions between up and down streams and limiting the role of brokers in the irrigation product marketing chain be future policy directions.